Efforts to Increase the Responsibility of Junior High School Students with Classical Guidance Service Tools - Zorifah Insaf Muharrifah (Bisma The Journal of Counseling, 2023)
The low sense of student responsibility is indicated by the attitude of students who do not submit assignments on time and are unable to complete assignments according to the instructions. This low sense of responsibility hurts the learning process and student outcomes. One of the efforts that can be made to overcome this problem is using classical guidance services for students. This study aims to develop and test the acceptability and effectiveness of classical guidance service tools to increase the responsibility of junior high school students. This research belongs to the development research using the 4D model (Define, Design, Develop, and Disseminate). Collecting data in the study was carried out using observation, interviews, and questionnaires. The instruments used are observation guidelines, product content validity instruments, and responsibility questionnaires. The data obtained in the study were then analyzed using the CVR (Content Validity Ratio) and CVI (Content Validity Index) formulas and t-tests. The results of the CVR analysis showed that all of the questionnaire item statements were accepted and obtained a CVI score of 1 with a very good category. Thus, the classical guidance service device complied with the acceptance requirements. The effectiveness of the classical guidance service device was tested on 35 junior high school students using the Pretest-Posttest Control Group Design experimental design. The results of the t-test formula test obtained a probability value or Sig. (2-tailed) of 0.000, this probability value is smaller than the 0.05 significance level. These results then show that using classical guidance service tools effectively increases the responsibility of junior high school students.